National hospice for the insane and the Brazilian Neurology in the beginning of the 20th century - Marleide da Mota Gomes; Maria Tavares Cavalcanti (Arquivos de Neuro-Psiquiatria)
The modern Brazilian Neurology was born in the campus of Praia Vermelha, Universidade Federal do Rio de Janeiro (UFRJ). The former National Hospice for the Insane (NHI) as well as some of its facilities were fundamental for the teaching about diseases of the nervous system to the students of the UFRJ's Medical School, caring for patients with neurosyphilis and epilepsy, as well as children with neurological impairment. We highlight the role of Juliano Moreira, director of the NHI (1903-1930), and his team, including Antonio Austregésilo Rodrigues Lima, the "father" of the Brazilian Neurology, in the construction of the modern Brazilian Psychiatry and Neurology.